(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In the contemporary digital landscape, data privacy has become an essential area of knowledge, particularly for young individuals, including students. The rapid advancement of information technology has significantly transformed the education system, offering substantial opportunities for students in higher education. However, concerns regarding data privacy and security have emerged alongside these opportunities. This study examines the level of awareness among students regarding data privacy and the measures they take to safeguard their personal information. A semi-structured questionnaire was used to collect the data needed to meet the aims. Employing a mixed-methods research design, the study integrates quantitative techniques—utilising tabulation with percentages—alongside qualitative approaches, such as case studies and theoretical descriptive analysis. The findings provide critical insights into students' awareness levels, contributing to the broader discourse on data privacy education in higher learning institutions.